Bimetal Schottky Heterojunction Boosting Energy‐Saving Hydrogen Production from Alkaline Water via Urea Electrocatalysis. (27th February 2020) - Wang, Chao; Lu, Haoliang; Mao, Zeyang; Yan, Chenglin; Shen, Guozhen; Wang, Xianfu
Abstract: Hydrogen production via water electrocatalysis is limited by the sluggish anodic oxygen evolution reaction (OER) that requires a high overpotential. In response, a urea‐assisted energy‐saving alkaline hydrogen‐production system has been investigated by replacing OER with a more oxidizable urea oxidation reaction (UOR). A bimetal heterostructure CoMn/CoMn2 O4 as a bifunctional catalyst is constructed in an alkaline system for both urea oxidation and hydrogen evolution reaction (HER). Based on the Schottky heterojunction structure, CoMn/CoMn2 O4 induces self‐driven charge transfer at the interface, which facilitates the absorption of reactant molecules and the fracture of chemical bonds, therefore triggering the decomposition of water and urea. As a result, the heterostructured electrode exhibits ultralow potentials of −0.069 and 1.32 V (vs reversible hydrogen electrode) to reach 10 mA cm −2 for HER and UOR, respectively, in alkaline solution, and the full urea electrolysis driven by CoMn/CoMn2 O4 delivers 10 mA cm −2 at a relatively low potential of 1.51 V and performs stably for more than 15 h. This represents a novel strategy of Mott–Schottky hybrids in electrocatalysts and should inspire the development of sustainable energy conversion by combining hydrogen production and sewage treatment. Abstract : A Schottky catalyst is constructed from a CoMn/CoMn2 O4 heterostructure for energy‐saving hydrogen production from alkaline solution via urea electrocatalysis. Benefiting from the interface electron redistribution, CoMn/CoMn2 O4 can synergistically facilitate the adsorption and fracture of the chemical groups in urea and water molecules and thus promote urea electrocatalysis.